PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM DAMPAKNYA TERHADAP FINANCIAL DESTRESS PADA PERUSAHAAN SEKTOR LOGAM TERDAFTAR DI BEI TAHUN 2014 - 2018 - Yulistina Yulistina; Dewi Silvia; Euis Miftahul (Jurnal Akuntansi dan Keuangan, 2020)
ABSTRACTThis study aims to determine the effect of the independent variables on the dependent variable, namely financial performance (return on assets, earnings per share, net profitmargins, debt equity ratio) and stock returns the impact on financial distress (bankruptcy) on metal manufacturing companies listed in The Indonesia Stock Exchange in 2014-2018was good. The analysis method uses the path analysis method with stock return variableas a mediating variable. The results showed that financial performance variables (ROA,EPS, NPM, DER) simultaneously had a positive and significant effect on stock returns based on the value of Fcalculate, where F arithmetic> F table (43,908> 2.58) and a significant value of sig 0 .00 <0.05. Financial performance variables (ROA, EPS, NPM,DER) simultaneously have a positive and significant effect on Financial Destress (Z-core)based on the calculated F. value, where F count> F table (15.761> 2.58). Stock Returnvariable partially has a positive and significant effect on the Financial Destress variablebased on the value of t arithmetic where t arithmetic> t table (2.505> 1.666), asignificance of 0.015 <0.05.